2023
DOI: 10.1590/0034-7167-2022-0020
|View full text |Cite
|
Sign up to set email alerts
|

Nursing care management concepts: scoping review

Abstract: Objectives: to clarify the concepts of Nursing Care Management and Nursing Care Administration in the scientific literature, highlighting approximations and distances between the terms. Methods: scoping review as per Joanna Briggs Institute protocol and preferred reporting items for Systematic Reviews and Meta-analysis extension for Scoping Reviews (PRISMA-ScR). The searches were performed in LILACS, CINAHL, MEDLINE, and Scopus databases. Results: the qualitative analysis, through content analysis, counted 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(157 reference statements)
0
1
0
2
Order By: Relevance
“…Quanto à enfermagem, no Brasil o enfermeiro tem atuação destacada na assistência, promoção, prevenção, proteção e recuperação da saúde, incluindo a gestão do cuidado e dos serviços de saúde 7 . No Chile, a enfermagem é uma profissão regulamentada, mas com fragilidades na definição de atribuições profissionais, o que pode contribuir para a vulnerabilidade de alguns pontos do sistema de saúde e do trabalho em equipe 8 .…”
Section: ____________________unclassified
“…Quanto à enfermagem, no Brasil o enfermeiro tem atuação destacada na assistência, promoção, prevenção, proteção e recuperação da saúde, incluindo a gestão do cuidado e dos serviços de saúde 7 . No Chile, a enfermagem é uma profissão regulamentada, mas com fragilidades na definição de atribuições profissionais, o que pode contribuir para a vulnerabilidade de alguns pontos do sistema de saúde e do trabalho em equipe 8 .…”
Section: ____________________unclassified
“…Some studies have shown that the postoperative recovery of colon cancer patients undergoing laparoscopic radical surgery is different. It is necessary to explore better nursing models to improve the surgical efficiency and nursing satisfaction of colon cancer patients [6]. Conventional nursing interven-Am J Transl Res 2024; 16(2):506-514 tions center on the patient's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Baseado no exposto, no âmbito do trabalho da equipe multiprofissional de saúde, a equipe de enfermagem é aquela que empreende o maior tempo de permanência junto à criança com cardiopatia reumática, fato que permite identificar com maior facilidade as necessidades de cuidado. Por se tratar de uma condição crônica de saúde, é premente que a gerência do cuidado, orientada para a melhoria da atenção e do cuidado direto ao cidadão 6 , seja realizada a partir de interações simbólicas que visem promover a qualidade de vida da criança e de sua família mediante ações que envolvam o cuidado a beira leito e o planejamento da assistência 7 .…”
unclassified